Intestinal dysbiosis and hormonal neuroendocrine secretion in the fibromyalgic patient - Tomasello, Giovanni; Mazzola, Margherita; Bosco, Vincenzo; Tomasello, Giulia; Damiani, Provvidenza; Sinagra, Emanuele; Carini, Francesco (Biomedical papers, 2018)
Fibromyalgia is a rheumatic syndrome and its pathogenesis is controversial. The recent literature has placed considerable attention on the link between alteration of the intestinal microbiota and fibromyalgia, emphasizing the close connection between the neuroenteric system and the CNS. This study aims to evaluate the probable relationship between intestinal dysbiosis and altered secretion of hormones and vitamins such as cortisol, serotonin, Vitamin D and thyroid hormones in a patient with fibromyalgia.
Keywords: microbiota; fibromyalgia; hormones; dysbiosis; serotonin; cortisol; vitamin D